A comparative study on the total reflection X‐ray fluorescence determination of low Z elements using X‐ray tube and synchrotron radiation as excitation sources. (20th January 2017) - Sanyal, K.; Kanrar, B.; Misra, N. L.; Czyzycki, M.; Migliori, A.; Karydas, A. G.
Abstract : Detailed total reflection X‐ray fluorescence (TXRF) studies for the detection and quantification of low atomic number elements were carried out by using a laboratory dual source TXRF spectrometer equipped with a vacuum chamber and at the International Atomic Energy Agency multi‐purpose end‐station facility, operated at the XRF beamline of Elettra Sincrotrone Trieste, Italy. Multi‐elemental standard aqueous solutions of low Z elements (F, Na, Al, S, K, Sc, and Ti) with different elemental concentrations of 2, 10, 20, and 30 µg/ml were prepared and measured in both setups. The measurements at the synchrotron setup were performed in a scanning mode across the sample residue and perpendicular to the incident beam in order to account properly for a possible non‐uniform deposition of certain elements. The accuracy and the detection limits obtained from the TXRF measurements in both setups were determined and comparatively evaluated and assessed. Significant improvement in the TXRF detection limits at the synchrotron beamline end‐station was obtained for the elements with Z ≤ 13 (Al). Copyright © 2017 John Wiley & Sons, Ltd.